“Nurses and health professionals facing female genital mutilation: a qualitative study “ - MIdoia Ugarte-Gurrutxaga; Victoria- Mazoteras-Pardo; Gonzalo Melgar de Corral; Brígida Molina-Gallego; Laura Mordillo-Mateos; Sagrario Gómez-Cantarino (BMC Nursing, 2023)
Abstract Background Transnational migratory movements make Spain a country with a very diverse population, including women and girls from countries where Female Genital Mutilation (FGM) is practiced. Given this reality, we set out to carry out a qualitative study to identify the knowledge, attitudes and skills of health professionals regarding FGM. Method Qualitative study with a content analysis approach. Forty-seven health professionals with the profiles of Nursing, Family Medicine, Pediatrics, Midwifery and Gynecology and Obstetrics were purposively selected. Data were collected through semi-structured in-depth interviews and focus groups. The qualitative content analysis approach was used for data analysis. The study was conducted in the years 2019 and 2022. Results Although most professionals are aware of the current legislation on FGM in Spain, only a few of them are aware of the existence of the FGM prevention protocol in Castilla-La Mancha. This lack of knowledge together with the perception that FGM belongs to the private sphere of women, contributes to the loss of opportunities to identify and prevent FGM. Conclusion Health professionals’ training, especially midwives and pediatricians, is essential to the identification and action against Female Genital Mutilation.